Sediment dynamics of mountain streams as a function of variation in sediment deposition - Nakanishi, Ryunosuke; Okajima, Yuki; Baba, Akira; Mitani, Yasuhiro; Ikemi, Hiro (Journal of Nepal Geological Society, 2018)
In Japan, the management of sediment in dam reservoirs has become challenging owing to heavy rain. Unexpected increase of sediment volume in dam reservoirs can increase flood risk owing to a rise in the level of the riverbed. It is therefore necessary to conduct sediment management to clarify the area of sediment production to control the amount of sediment transported and the timing of its movement. Sediment discharge from tributaries is often calculated based on catchment area and the deposited sediment volume already present in the dam reservoir. However, our preliminary surveys have implied that it is also necessary to consider regional geology in the evaluation of sediment transport. Moreover, variations in sediment deposition should be evaluated for each site where the geology changes. In this study, we observe in detail changes in the riverbed in two tributaries with different regional geologies. Changes in the shape of the riverbed were analyzed from unmanned aerial vehicle observation data, following which the effects of erosion and sedimentation on the riverbed were quantitatively evaluated. Finally, sediment discharge was calculated by a one-dimensional numerical model of sediment transport. These results indicate that the tributary that is mostly composed of mudstone produced considerably more sediment than the tributary composed mainly of sandstone. This suggests that an understanding of regional geology is necessary in the evaluation of sediment dynamics and should be considered in addition to the catchment area.